A cellular protection racket: How lysosomal Ca2+ fluxes prevent kidney injury. (January 2021) - Galione, Antony; Davis, Lianne C.; Morgan, Anthony J.
Graphical abstract: Highlights: LC3, an autophagic protein, may operate non-canonically to mediate cellular responses independent of canonical autophagy. Lipidated LC3 physically interacts with TRPML1. Lipidated LC3 activates TRPML1. Lipidated LC3 is required for the translocation of TFEB into the nucleus. Lipidated LC3 is required for the lysosomal damage response, eg in crystal nephropathy. Abstract: LC3-lipidation is activated by lysosomal damage by mechanisms that are unknown and divergent from canonical autophagy. In this study, Nakamura et al, show that lysosomal damage induced by lysosomotropic agents or oxalate in renal proximal tubule cells causes lipidated LC3 to insert into the lysosomal membrane to activate TRPML1 channels and release Ca 2+ from lysosomes. This leads to TFEB dephosphorylation and translocation into the nucleus which results in clearance of damaged lysosomes and their contents which may reduce the deleterious effects of crystal nephropathy.